FORMULATION AND EVALUATION OF TOPICAL ANTI-INFLAMMATORY HERBAL GEL - MAHENDRA A GIRI; RASIKA D BHALKE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present investigation aims at development and evaluation of herbal anti-inflammatory gel using of methanolic extract from Emblica officinalis fruits (MEEOF) and Aegle marmelos fruits (MEAMF). Methods: The gels were prepared using Carbopol 934, various concentrations of MEEOF, MEAMF, propylene glycol 400, methylparaben, propylparaben, and required amount of distilled water. Then, skin pH (6.8-7) was maintained by dropwise addition of triethanolamine. Prepared formulations were evaluated for physical appearance, pH, spreadability, viscosity and homogeneity, skin irritation on animal model (rabbit), and anti-inflammatory activity using carrageenan-induced rat paw edema model on albino Wistar rats of either sex (150–200 g). Change in edema volume of the rat hind paw was measured, and percent inhibition was calculated. ICH guidelines have followed for stability studies. Results: Results reveal that gel showed good appearance, homogeneity, and spreadability. Viscosity is ranging between 4200 and 4500 centipoises. All formulations have shown no skin irritation to animals. Formulations F4 and F5 significantly inhibited the inflammation to the extent of 56.66%, 61.66% at 3 h and 59.21%, 63.15% at 4 h, respectively, while the reference drug reduced the inflammation by 66.66% at 3 h and 76.31% at 4 h. The preparation was stable under normal storage conditions and did not produce any skin irritation, i.e., erythema and edema when applied over the skin on storage. Conclusion: It was concluded that anti-inflammatory effect of F4 and F5 was comparable to standard.